TTK Group's "SKORE": scoring in the condom industry. Issue 1 (30th January 2020) - Kamath, Renuka
Abstract : Learning outcomes: To appreciate the link of marketing strategy in terms of a brand launch, implementation and sustainability for business growth; to appreciate the complexity of consumer behavior in the purchase and usage journey of consumers for condoms; to analyze the nature of competition for the entry of a differentiated new brand; to analyze points-of-parity and points-of differentiation for uniquely positioning a new brand in the condom category; and to examine, analyze and evaluate strategic options for the next stage of growth. To make choices from the options. Case overview/synopsis: Vishal Vyas, General Manager Marketing, TTK Protective Devices Limited (TTKPDL), had been a part of the exciting journey of launching SKORE, their new brand of condoms. In 2010, the company found itself in a rather unusual circumstance when it lost its rights to the most successful condom brands in the country. However, they had with them their sales and marketing expertise, a good team and a strong and loyal network of retailers. TTKPDL decided to enter the rather crowded Indian condom market and launch a new brand, SKORE. As a product category, condoms were particularly complex, socially, as well as in attitude toward their purchase and usage. SKORE went on to optimally using marketing strategy and gaining a strong foothold by capturing market share from strong players with a differentiated positioning of a brand that was youthful and quirky. By 2017 after having steadily grown the brand, Vyas was now looking for the next level of growth in a market, which not only appeared to be stagnating but also one where competitive activity was increasing. He was considering different options for SKORE's growth. For TTKPDL, the strategic choice may be between expanding to new markets and new segments of consumers or capturing more of their currently defined target group or both. If they wanted to do something different, should they also look at expanding their product portfolio? Vyas needed to decide on the next move. Complexity academic level: This case can be used in the core MBA Marketing Management course or core marketing course in the executive education program to highlight the important link of marketing strategy to business strategy. It can also find a place in marketing strategy and consumer behavior courses. It clearly demonstrates the launch and implementation of a new brand in a cluttered market of a sensitive product category and considers strategic options for further growth. The case is designed to help students appreciate consumer behavior for a sensitive product category and the entry of a new brand with five strong brands leading the market. It guides students toward looking at different options for the next level of growth and making recommendations. Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS 8: Marketing.